Characteristics of BCR::ABL1 kinase domain mutations in Vietnamese chronic myeloid leukemia patients - Phu Chi Dung; Huynh Duc Vinh Phu; Cao Van Dong; Chau Thuy Ha; Nguyen Thi Thanh Ha; Tran Ngoc Xuan Thy; Le Vu Ha Thanh; Huynh Nghia; Nguyen Tan Binh; Hoang Anh Vu; Phan Thi Xinh; Cao Sy Luan (Leukemia Research Reports)
Background: BCR::ABL1 kinase domain (KD) mutations represent a common cause of resistance to tyrosine kinase inhibitors in chronic myeloid leukemia (CML) patients. The frequency and pattern of KD mutations differ among populations worldwide. However, the characteristics of KD mutations in Vietnamese patients remain unclear. Methods: A retrospective cohort study of CML patients at Blood Transfusion Hematology Hospital who were resistant to frontline imatinib between Oct 2010 and Oct 2018. Direct sequencing technique was performed to detect KD mutations. Results: 488 imatinib-resistant CML patients were included in our study. The median age of the patients was 39, with the majority (82.1 %) diagnosed with chronic phase at the time of resistance. KD mutations were identified in 173 (35.5 %) patients, with 8 cases involving novel variants. The KD mutations predominantly localized within the P-loop of BCR::ABL1 (36.7 %). G250E was the most common mutation, followed by Y253H, M351T, and M244V. In particular, Y253H, T315I, F359V, F317L, E355G, and Q252H were frequently observed in accelerated phase and blast crisis patients. In addition, M244V, T315I, E459K, E255K, F317L, Q252H and E355G were all observed in primary resistant patients. Conclusion: The emergence of certain specific mutations may serve as the early indicators of leukemic progression, necessitating prompt intervention for better disease control.